1997
DOI: 10.2307/3579412
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Lung Cancer Mortality from Residential Radon Using Data for Low Exposures of Miners

Abstract: Some recent estimates of lung cancer risk from exposure to radon progeny in homes have been based on models developed from a pooled analysis of 11 cohorts of underground miners exposed to radon. While some miners were exposed to over 10,000 working level months (WLM), mean exposure among exposed miners was 162 WLM, about 10 times the exposure from lifetime residence in an average house and about three times the exposure from lifetime residence at the "action level" suggested by the U.S. Environmental Protectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(39 citation statements)
references
References 25 publications
3
34
0
2
Order By: Relevance
“…An advantage of this approach is that estimates of the independent effect of exposure during each window may be obtained (Ha et al 2007; Lubin et al 1997). However, the approach is not always feasible because of collinearity issues (e.g., inflated standard errors, unstable regression coefficients).…”
Section: Methodsmentioning
confidence: 99%
“…An advantage of this approach is that estimates of the independent effect of exposure during each window may be obtained (Ha et al 2007; Lubin et al 1997). However, the approach is not always feasible because of collinearity issues (e.g., inflated standard errors, unstable regression coefficients).…”
Section: Methodsmentioning
confidence: 99%
“…In most cases linear extrapolation and excess relative risk (ERR) per unit exposure derived from the miners' data have been used to estimate risks at low doses [2,3]. However, in practice large differences in ERR (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…lung cancer) has not yet been satisfactorily defined and continues to be the subject of discussion and analysis. In spite of the different radon exposure conditions in homes and mines, studies of lung cancer incidence among uranium miners still form the most important source of information for estimating the risk of lung cancer in the population from indoor radon exposure [1][2][3][4]. The studies of different cohorts of uranium miners [1,2,5] have clearly shown that high levels of radon exposure can cause lung cancer and evidence has been provided that even when data from exposures as low as 50 and 100 WLM (Working Level Months, a measure of the exposure to radon used for the miners) are considered, increased levels of lung cancer have been observed [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Radon further decays into a series of radon daughters that emit alpha particles. Underground miners exposed to high levels of radon gas in the past have been shown to be at increased risk of lung cancer (Lubin et al, 1995(Lubin et al, , 1997. These epidemiological observations have resulted in the designation of radon as a risk factor for lung cancer in humans by the International Agency for Research on Cancer (1988).…”
Section: Introductionmentioning
confidence: 99%